OPTIMALISASI PENGELOLAAN ZAKAT, INFAK/SEDEKAH TERHADAP PROSES KEMANDIRIAN MASYARAKAT (STUDI PADA LEMBAGA AMIL ZAKAT (LAZ) SWADAYA UMMAH KOTA PEKANBARU) - AGUS SETIAWATI; TUTI KHAIRANI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Optimalization Management of Religious obligatory, Infaq/Shodaqoh ToProcess Independence Society (Study At Institute of Amil Religious Obligatory (Self-Supporting (Laz) of Ummah Town of Pekanbaru). This Research aim to to know and getclear picture about accurate by phenomenon that is how optimalization management ofreligious obligatory, infaq/shodaqoh to society independence process and also factors anykind of influencing optimalization management of religious obligatory, infaq/shodaqoh tosociety independence process. To analyse phenomenon in this research writer use theory ofGeorge R.Terry with indicator attainment of efficacy seen to start from planning process,organizational, movement, and observation. Methodologies which is used in this research isresearch qualitative. Result of research show that Institute of Amil Self-Supporting Religiousobligatory of Ummah have been able to become self-supporting institute of society able togive benefit to all dhuafa requiring, special but a] economic area of Self-Supporting LAZ ofUmmah still not yet optimal in the effort self-supporting all dhuafa, this matter can be seenfrom amount of dhuafa able to be assisted by Self-Supporting LAZ of Ummah still not yetfulfilled goals eradication of poorness in town of Pekanbaru. Besides amount of given capitaldo not be big so so that all dhuafa only can found small industry like effort or haberdasherryof sells in cloisterKeyword : Religious obligatory, Infaq, Mustahiq